S04-3: Back to a Healthy Society (BASE): Results, Impact, and Learnings of the BASE Project in Local Communities in Lithuania, North Macedonia, The Netherlands, and Spain (Baltic Journal of Sport and Health Sciences, 2026)
The project Back to a Healthy Society (BASE) aims to (re)connect older adults to society so that they can improve and enjoy a healthier lifestyle. To achieve this objective, an activation process in which older adults themselves take on a leading role is promoted. The BASE project has been experimentally implemented in communities across four European countries: Lithuania, North Macedonia, the Netherlands, and Spain. In the first phase, 11 professionals (international mentors) from those countries were selected based on their solid theoretical and practical expertise in promoting healthy lifestyles among older adults at the community level. They received specialised training to enhance their skills and commitment, enabling them to guide the professional development of local mentors within the active neighbourhood framework.During the second phase, these international mentors trained 42 local mentors (i.e. sports professionals with experience in healthy lifestyle promotion for older adults), equipping them with the knowledge to sustainably support local change agents in implementing the active neighbourhood approach.In the third phase, a total of 80 local change agents (Buddies) were trained by the local mentors. Using a learning-by-doing methodology, the Buddies acquire competencies through real-life experiences with the mentors’ guidance. These buddies are older adults with prior experience as participants in healthy lifestyle programmes who demonstrate leadership potential for active ageing initiatives in their communities.To date, the healthy lifestyle activities conducted in collaboration with the Buddies have engaged over 1,000 participants, many of whom were first-time attendees in such programmes. It should be noted that more multiplier activities will be implemented in the coming months, with more comprehensive impact data expected soon.However, assessing the project’s actual impact is complex and cannot be reduced to a single metric. The initiative has generated significant community engagement, and preliminary outcomes are highly promising. Beyond immediate effects, the project is designed to yield medium- and long-term impacts. An increasing number of neighbourhoods have expressed interest in adopting this approach, and the project’s experiences may serve as a roadmap for future implementations.Acknowledgement: The Erasmus+ BASE project was co-funded by the European Union.Keywords: Older adults, healthy lifestyle, healthy living, peer-to-peer, community-based social change, mentorship, active ageing